2021
DOI: 10.1042/bcj20200996
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of hydroxymethylbilane synthase complexed with a substrate analog: a single substrate-binding site for four consecutive condensation steps

Abstract: Hydroxymethylbilane synthase (HMBS), which is involved in the heme biosynthesis pathway, has a dipyrromethane cofactor and combines four porphobilinogen (PBG) molecules to form a linear tetrapyrrole, hydroxymethylbilane. Enzyme kinetic study of human HMBS using a PBG-derivative, 2-iodoporphobilinogen (2-I-PBG), exhibited noncompetitive inhibition with the inhibition constant being 5.4 ± 0.3 µM. To elucidate the reaction mechanism of HMBS in detail, crystal structure analysis of 2-I-PBG-bound holo-HMBS and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 56 publications
4
32
0
Order By: Relevance
“…This suggests that the role of this loop is incidental to the catalytic sequence of events, at least up to ES 2 . However, Sato et al (2021) report that 'flexibility of this loop in the proximity of the active site appears to be involved in the binding of 2-I-PBG and the substrate, although no direct interactions between the loop (residues 58-69) and 2-I-PBG were observed'. This last sentence seems to be a little self-contradictory.…”
Section: Consistency Of the Active-site Structures Of The Es 2 Intermediatementioning
confidence: 97%
See 3 more Smart Citations
“…This suggests that the role of this loop is incidental to the catalytic sequence of events, at least up to ES 2 . However, Sato et al (2021) report that 'flexibility of this loop in the proximity of the active site appears to be involved in the binding of 2-I-PBG and the substrate, although no direct interactions between the loop (residues 58-69) and 2-I-PBG were observed'. This last sentence seems to be a little self-contradictory.…”
Section: Consistency Of the Active-site Structures Of The Es 2 Intermediatementioning
confidence: 97%
“…They also reported that 'The overall structure of the 2-I-PBG-bound holo-HMBS was found to be similar to that of the inhibitor-free holo-HMBS'. Table 2 of Sato et al (2021) provides comprehensive details of the interactions between pyrroles and the protein moiety in HMBS (in their four crystal structures). Fig.…”
Section: Commentary On the Role Of The Pdb Data Files In Structural And Functional Studies Of Hmbsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a significant, complementary observation to the electron density map changes in the enzyme active site. Subsequent to these experiments the human HMBS enzyme has been studied by static X-ray crystallography in the apo and ES2 forms by trapping of this state (Pluta et al, 2018;Kallio et al, 2021;Sato et al, 2021). The two approaches, time-resolved and static crystallography, yield complementary views of the intermediate structures, ES2.…”
Section: Realizing Ultimate Precision Via Transfer Of Ligand Charge Density Results To Protein As Ligand Bindermentioning
confidence: 99%